The Prospective Association of Dietary Sugar Intake in Adolescence With Risk Markers of Type 2 Diabetes in Young Adulthood - Della Corte, Karen A.; Penczynski, Katharina; Kuhnle, Gunter; Perrar, Ines; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Remer, Thomas; Alexy, Ute; Buyken, Anette E. (Frontiers in Nutrition, 2021)
Purpose: To examine the prospective relevance of dietary sugar intake (based on dietary data as well as urinary excretion data) independent of food source in adolescent years for insulin sensitivity and biomarkers of inflammation in young adulthood. Methods: Overall 254 participants of the DONALD study who had at least two 3-day weighed dietary records for calculating intakes of fructose, glucose, sucrose, total, free and added sugars or at least two complete 24-h urine samples (n=221) for calculating sugar excretion (urinary fructose and urinary fructose+sucrose) in adolescence (females: 9-15 y, males: 10-16 y) and a fasting blood sample in adulthood (18–36 years), were included in multivariable linear regression analyses assessing their prospective associations with adult homeostasis model assessment insulin sensitivity (HOMA2-%S) and a pro-inflammatory score (based on CRP, IL-6, IL-18, leptin, chemerin, adiponectin). Results: On the dietary intake level, no prospective associations were observed between adolescent fructose, sucrose, glucose, added, free or total sugar intake and adult HOMA2-%S (p>0.01). On the urinary level, however, higher excreted fructose levels were associated with improved adult HOMA2-%S (p=0.008) among females only. No associations were observed between dietary or urinary sugars and the adult pro-inflammatory score (p>0.01). Conclusion: The present study cannot provide support that dietary sugar consumed in adolescence is associated with adult insulin sensitivity. The one potential exception is the moderate dietary consumption of fructose, which showed a beneficial association with adult fasting insulin and insulin sensitivity.